Transvaginal ultrasonography in women with postmenopausal bleeding - Rathnayaka, R.M.P.D (My University, 2005)
The purpose of this study was to validate the use of trans-vaginal ultrasonography in the assessment of endometrial abnormalities in women with postmenopausal vaginal bleeding. One hundred and twenty three patients with postmenopausal bleeding were subjected to transvaginal scan to measure the endometrial thickness and to see the endometrialmyometrial interface regularity. Dilatation and curettage was perfomed on all patients. Histopathological diagnosis was compared with the endometrial thickness found. Cut-off value of endometrial thickness to diagnose any abnormality, its sensitivity, specificity, positive and negative predictive value were calculated. Abnormal endometrial histopathology for the postmenopausal women was found in 51 (41.5 percentage) out of 123 patients. Receiver operating characteristic curve analysis revealed 3mm to be the optimal endometrial thickness cut-off for diagnosing endometrial abnormalities. Transvaginal scan is a valid method in the assessment of endometrial abnormalities in women with postmenopausal bleeding per vagina. Cut-off value of 3mm is the optimal endometrial thickness for the diagnosis of endometrial pathology.